Effect of temperature and density on the survival rate of transportation nener milkfish Chanos chanos - Muhammad Bakri; Wa Ode Nurlin; Fendi Fendi (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2019)
The study aims to determine the optimum temperature, optimum density and optimum temperature and density interactions in milkfish (Chanos chanos) transportation. This research was conducted in 2016, in Kendari City, Southeast Sulawesi Province. This study uses a factorial design, consisting of Temperature and Density Factors. The design of the combination treatment of Temperature (A) namely Temperature 15 oC, A2 Temperature 18 oC, A3 Temperature 21 oC. For Density Factor (B), B1 Density of 600 individuals / container, B2 Density of 800 individuals / container, B3 Density of 1,000 individuals / container. The results of analysis of variance at 95% and 99% confidence level, the treatment in this study had no significant effect, where the F count is smaller than the F table. This shows that the combination of temperature and density tested in this study can be used for energy transportation activities for 14 hours. Based on the percentage of graduation of nener life tested in the transportation, starting from the biggest graduation to the smallest life pass, is a combination of 15 oC temperature treatment and a density of 1000 individuals 95.57%, a combination of 18 oC temperature treatment and a density of 800 individuals 95.04 %, a combination of temperature treatment of 21 oC and density of 1000 individuals 91.70%, combination of temperature treatment of 15 oC and density of 800 individuals 90.04%, combination of temperature treatment of 15 oC and density of 600 individuals 89.89%, combination of temperature treatment of 21 oC and a density of 800 individuals 88.67%, a combination of temperature treatment 18 oC and a density of 1000 individuals 88.07%, a combination of temperature treatment 21 oC and a density of 600 individuals 84.33% and a combination of temperature treatment 18 oC and density of 600 individuals 73.28%.